Terrorism: Major threat to Pakistan’s National Security - Dr. Aisha Khanum (Journal of Political Studies, 2007)
In the new literature on national security, internal factors are equally and sometimes more important than the traditional factors. The state of Pakistan at the moment has a stronger challenge to its security from the internal factors as compared to external. Pakistan faces multi forms of terrorism, no other country in the world is entangled in this problem as the Pakistan of today. Ethnic terrorism which led to the dismemberment of Pakistan in 1971 resurfaced again on the question of linguistic differences in the some parts of the country but has been brought under control with the mainstreaming of ethnic political parties. Nationalist terrorism has mainly been witnessed in province of Balochistan at regular intervals and mainly revolves around the issues of exploitation of resources and threat to the political identity and culture of minorities sub-nationalities. Sectarianism in Pakistan was an extended version of rivalries between Northern Alliance and certain Sunni factions in Afghanistan and an aftermath of Iran & Iraq war, Jehadi terrorism which emerged in the post 9/11 scenario is by far the most serious threat to Pakistan so far because of its role as the front line state in war against terrorism. The tension between ultra conservative and moderate followers of Islam is mounting and weakening the sate structure. It is beyond the capacity of a single person or a one time effort to eradicate the deep rooted problem from the society. An institutional mechanism with wide ranging participation on regular and permanent basis is the only way to fight this menace.